Highly thermally conductive flowable silicone composition
Patent Information
- Application Number
- JP2022529962
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-05
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2039-12-05
Smart Images

Figure 0007651571000001 
Figure 0007651571000002
Abstract
Description
[Background technology]
[0001] FIELD OF THEINVENTION The present invention relates to a thermally conductive composition that contains a combination of four different sizes of filler particles.
[0002] Introduction Ever-increasing performance requirements for electronic devices are driving the need for electronic circuits to support ever-higher power density requirements, which in turn drives increased heat dissipation requirements for the circuits to remove the heat generated by the increased power density.
[0003] Thermally conductive materials used to dissipate heat between elements of a circuit are often polyorganosiloxane matrices highly filled with thermally conductive fillers. Thermally conductive materials are placed between elements of a circuit to conduct heat from one element to another in order to dissipate heat within the circuit. Increasing the concentration of thermally conductive fillers increases the thermal conductivity of the thermally conductive material, but also increases the viscosity of the material. There is a challenge in obtaining the highest possible thermal conductivity while still maintaining a low enough viscosity (extrudability) so that the material can be effectively processed and applied. A specific objective of the present invention is to identify a thermally conductive material that has a thermal conductivity greater than 7.5 watts / meter*Kelvin (W / m*K) and good processability, defined as having an extrusion rate of 50 grams per minute as determined by the extrusion rate test described below.
[0004] Patent application PCT / CN2018 / 125408 discloses a thermally conductive material with a polyorganosiloxane matrix containing three thermally conductive fillers in a specific distribution, one of which is large-sized magnesium oxide (MgO) filler particles. One example INV-7 in this reference shows that a thermally conductive material containing 129 micrometer magnesium oxide (MgO) particles can achieve a thermal conductivity of more than 7.5 W / m*K and a flow rate of more than 50 g / min.
[0005] US Patent Application Publication No. 20180127629 discloses a thermally conductive material using a polyorganosiloxane material containing a thermally conductive filler in a specific distribution. Two of the examples in this reference (Examples 3 and 4) show a thermal conductivity of more than 7.5 W / m*K. It is unclear what the extrusion amount of the material was. Examples 1 to 10 in this reference use a surface treatment agent that is a specific vinyl-functional siloxane molecule, and the results of these examples show that a thermal conductivity of more than 7.5 W / m*K is achieved only when the loading amount of this treatment agent is 1.0 part, and above or below this loading level, the thermal conductivity is less than 7.5 W / m*K. These results clearly show that the desired thermal conductivity is achieved only at a specific loading amount of a specific surface treatment agent.
[0006] It would be desirable to identify a polyorganosiloxane-based thermally conductive material that can achieve a thermal conductivity of greater than 7.5 W / m*K and a flow rate of greater than 50 g / min as determined by extrusion rate testing without the need for 129 micrometer MgO particles as required in PCT / CN2018 / 125408 or specific vinyl-functional surface treatment agents at specific concentrations as required in US20180127629. Even more desirable would be such a thermally conductive material that can achieve a thermal conductivity of 8.0 W / m*K or greater, or even 9.0 W / m*K or greater, which is not achieved in any of these references. Summary of the Invention
[0007] The present invention provides a solution to the problem of finding a polyorganosiloxane-based thermally conductive material that can achieve a thermal conductivity of greater than 7.5 W / m*K and a flow rate of greater than 50 g / min as determined by extrusion rate testing without the need for 129 micrometer MgO particles, or any MgO particles, as required in PCT / CN2018 / 125408, or the specific vinyl-functional surface treatment agent at a specific concentration, as required in US20180127629. The present invention can even achieve a thermal conductivity of 8.0 W / m*K or greater, or even 9.0 W / m*K or greater.
[0008] The present invention is the result of the discovery of a particular combination of thermally conductive fillers and surface treatments that both achieve the desired flow properties and also provide unexpectedly high thermal conductivity.
[0009] In a first aspect, the present invention provides a combination of (a) a polyorganosiloxane component comprising one or a combination of two or more polyorganosiloxanes; (b) a filler treating agent comprising an alkyltrialkoxysilane and a trialkoxysiloxy terminated diorganopolysiloxane; and (c) 90 to 98 weight percent of a thermally conductive filler, the combination comprising: (i) 25 to 40 weight percent of thermally conductive filler particles having an average particle size of 70 to 150 micrometers and selected from one or a combination of aluminum oxide particles and aluminum nitride particles; and (ii) 3 (iii) 25 to 32 weight percent of aluminum oxide particles having an average particle size in the range of 1 to 5 micrometers; and (iv) 10 to 15 weight percent of thermally conductive filler particles having an average particle size in the range of 0.1 to 0.5 micrometers, wherein the weight percentages are based on the weight of the composition.
[0010] In a second aspect, the invention is an article of manufacture comprising the composition of the first aspect interposed along a thermal pathway between two objects.
[0011] The present invention is useful as a thermally conductive material in electronic circuits to aid in the dissipation of heat. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Test methods refer to the test method most recent as of the priority date of this document unless a date is given with the test method number. Reference to a test method includes both a reference to the testing society and the test method number. The following test method abbreviations and designations apply herein: ASTM refers to the American Society for Testing and Materials, EN refers to European Norm, DIN refers to the Deutsches Institut fur Normung, ISO refers to the International Organization for Standards, and UL refers to the Underwriters Laboratory.
[0013] Products identified by trade names refer to compositions available under those trade names as of the priority date of this document.
[0014] "Plurality" means two or more. "And / or" means "and, or alternatively." All ranges include endpoints unless otherwise indicated. All weight percent (wt%) values are by weight of the composition and all volume percent (vv%) values are by volume of the composition unless otherwise indicated. Viscosity is determined according to ASTM D-445, IP71 using a glass capillary viscometer (CTM0004A). The kinematic viscosity of a liquid sample is determined by measuring the time it takes for a volume of the sample liquid to flow by gravity through a calibrated glass capillary.
[0015] The composition of the present invention includes a polyorganosiloxane component that includes one or a combination of two or more polyorganosiloxanes. In the broadest scope of the present invention, the polyorganosiloxane component can include any polyorganosiloxane. Desirably, the polyorganosiloxane component includes a polyorganosiloxane having one or more carbon-carbon unsaturated bonds, preferably carbon-carbon double bonds, more preferably in the form of vinyl groups. In addition, it is desirable for the polyorganosiloxane component to have a polyorganosiloxane that contains silylhydride functional groups (Si-H), preferably multiple silylhydride functional groups per molecule. The carbon-carbon unsaturated groups and / or silylhydride groups may be located at pendant or terminal positions along the polyorganosiloxane chain. The polyorganosiloxane containing carbon-carbon unsaturated bonds and the polyorganosiloxane containing silylhydride functional groups may be the same polyorganosiloxane or different polyorganosiloxanes. When the polyorganosiloxane component includes a polyorganosiloxane having carbon-carbon unsaturated bonds and silylhydride functional groups, the polyorganosiloxane component can undergo hydrosilylation reactions to build viscosity, crosslink, gel, or cure into a hard composition as required. The polyorganosiloxane component may also or alternatively include one or more polyorganosiloxanes having one or more silylalkoxide groups (Si-OR), where "R" corresponds to a hydrocarbyl group as used herein, including substituted hydrocarbyl groups, which are hydrocarbyl groups in which one or more carbons and / or hydrogens are replaced with other atoms or chemical moieties, such as fluorine, oxygen, hydroxyl, or alkoxy).
[0016] Examples of suitable polyorganosiloxanes having carbon-carbon unsaturated bonds include those represented by the following general formula (I): ViR2SiO-(R2SiO) a -SiR2Vi (I) and vinyl-capped polydiorganosiloxanes such as those having the formula: where "Vi" corresponds to a vinyl group (-CH=CH2), R is independently selected from hydrocarbyl groups having 1 to 12 carbons at each occurrence, and the subscript "a" corresponds to the average number of ((CH3)2SiO) siloxane units per molecule. The hydrocarbyl group may be a substituted hydrocarbyl. Desirably, the hydrocarbyl group is selected from methyl and phenyl groups, and is preferably a methyl group. The subscript "a" is desirably 5 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, 40 or more, 45 or more, 50 or more, or even 55 or more, and at the same time is generally 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, or even 60 or less. 29 Si, 13 C and 1 H nuclear magnetic resonance spectroscopy is used to determine the values of subscripts such as "a" (as well as the subscripts "b," "c," "d," "e," "f," and "g" used in the formula below).
[0017] Examples of suitable polyorganosiloxanes having silylhydride functionality include polydimethylsiloxane molecules in which some of the methyl groups have been replaced with hydrogen atoms. Suitable examples include those having the following general formula (II): (CH3)3Si((CH3)2SiO) b ~((CH3)HSiO) c Si(CH3)3(II) and where the subscript "b" indicates the average number of ((CH3)2SiO) siloxane units per molecule, and the subscript "c" indicates the average number of ((CH3)HSiO) siloxane units per molecule. The "~" indicates that the ((CH3)2SiO) and ((CH3)HSiO) groups may be present in blocks or randomly distributed in any grouping, provided that the total number of ((CH3)2SiO) groups is b and the total number of ((CH3)HSiO) groups is c. The subscript "b" desirably has a value of 5 or more, 7 or more, 10 or more, 15 or more, or even 20 or more, and at the same time is generally 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 15 or less, or even 10 or less. The subscript "c" is desirably 1 or more, 2 or more, 3 or more, 4 or more, or even 5 or more, while generally 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less.
[0018] In general, it is desirable for the composition to have a polyorganosiloxane content of 4.0 weight percent (wt%) or less, preferably 3.75 wt% or less, or even 3.5 wt% or less, and 2.5 wt% or more, preferably 2.75 wt% or more, 2.9 wt% or more, or even 3.0 wt% or more, based on the weight of the composition.
[0019] The composition may have a carboxyl group content of at least 0.47 wt.%, at least 0.48 wt.%, at least 0.49 wt.%, at least 0.50 wt.%, at least 0.51 wt.%, at least 0.52 wt.%, at least 0.53 wt.%, at least 0.54 wt.%, at least 0.55 wt.%, at least 0.56 wt.%, at least 0.57 wt.%, at least 0.58 wt.%, or even at least 0.59 wt.%, and at the same time at most 0.62 wt.%, at most 0.61 wt.%, at most 0.60 wt.%, at most 0.59 wt.%, at most 0.58 wt.%, at most 0.57 wt.%, at most 0.56 wt.%, at most 0.55 wt.%, at most 0.54 wt.%, at most 0.53 wt.%, or even at most 0.52 wt.%, based on the weight of the composition. In combination with one or two polydimethylsiloxane molecules present in a concentration (combined concentration if two or more), the polyorganosiloxane having carbon-carbon unsaturated bonds, preferably vinyl-capped polydimethylsiloxane, may be present in an amount of at least 2.0 wt.%, at least 2.1 wt.%, at least 2.2 wt.%, at least 2.3 wt.%, at least 2.4 wt.%, at least 2.5 wt.%, at least 2.6 wt.%, at least 2.7 wt.%, or even at least 2.9 wt.%, and at the same time at most 3.0 wt.%, at most 2.9 wt.%, at most 2.8 wt.%, at most 2.6 wt.%, at most 2.5 wt.%, or even at most 2.4 wt.%, based on the weight of the composition.
[0020] The compositions of the present invention contain a filler treating agent which comprises both an alkyltrialkoxysilane and a trialkoxysiloxy-terminated diorganopolysiloxane.
[0021] Alkyltrialkoxysilanes have the general formula: (R')(R"O)3Si, where R' is desirably an alkyl having an average of at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, or even at least 16 carbon atoms per molecule, and generally at most 18 carbon atoms, and may have at most 17, at most 16, at most 15, at most 14, at most 13, at most 12, at most 11, or even at most 10 carbon atoms; and R" is desirably an alkyl having at least 1, at least 2, at least 3, at least 4, at least 5, or even at most 6 carbon atoms, and generally at most 10, at most 9, at most 8, at most 7, at most 6, at most 5, at most 4, at most 3, or even at most 2 carbon atoms. Desirably, the alkyltrialkoxysilane is an alkyltrimethoxysilane having the above alkyl group. One example of a desirable alkyltrialkoxysilane is decyltrimethoxysilane. The concentration of the alkyltrialkoxysilane is generally 0.20% by weight or more, 0.22% by weight or more, 0.24% by weight or more, and at the same time 0.30% by weight or less, preferably 0.28% by weight or less, 0.26% by weight or less, or 0.24% by weight or less, and may be 0.22% by weight or less, based on the weight of the composition.
[0022] Trialkoxysiloxy-terminated diorganopolysiloxanes generally have the following formula (III): R3SiO-(R2SiO) d -[(CH2) e ((CH3)2SiO) f ] g -(CH2) e -Si(OR")3(III) wherein R and R″ are each independently as defined above in each occurrence; the subscript “d” is the average number of (RSiO) units per molecule and generally has a value of 10 or more, 15 or more, 20 or more, 25 or more, or even 30 or more, and at the same time generally is 150 or less, 140 or less, 130 or less, 120 or less, 110 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 45 or less, 40 or less, 35 or less, or even 30 or less; The letter "e" independently has a value of zero or more, 1 or more, or even 2 or more, at each occurrence, and generally is 4 or less, 3 or less, or even 2 or less; the subscript "f" generally has a value of zero or more, 1 or more, 2 or more, 3 or more, and generally is 6 or less, 5 or less, 4 or less, 3 or less, or even 2 or less; and the subscript "g" generally has a value of zero or more, 1 or more, 2 or more, 3 or more, or even 4 or more, and generally is 6 or less, 5 or less, 4 or less, or even 3 or less.
[0023] Desirably, the trialkoxysiloxy-terminated diorganopolysiloxane has the general formula (IV): (CH3)3SiO((CH3)2SiO) d Si(OR")3(IV) One particularly desirable trialkoxysiloxy-terminated diorganopolysiloxane has a composition of formula (IV) in which R″ forming the terminal trimethoxy-functionalized silicon atom is equal to methyl, and subscript “d” is equal to a value of 130 or less, preferably 120 or less, preferably 110 or less, more preferably 110 or less or 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, or 30 or less, and simultaneously greater than 20, preferably greater than 30.
[0024] The concentration of trialkoxysiloxy-terminated dimethylpolysiloxane siloxane is generally greater than or equal to 1.0 wt.%, greater than or equal to 1.05 wt.%, or even greater than or equal to 1.10 wt.%, and at the same time less than or equal to 1.20 wt.%, less than or equal to 1.15 wt.%, or even less than or equal to 1.10 wt.%, based on the weight of the composition.
[0025] The composition of the present invention comprises a combination of four different sizes of thermally conductive filler particles: (i) large size, (ii) medium size, (iii) small size, and (iv) fine size. The average particle size of the filler particles is measured as the volume-weighted median of the particle size distribution (Dv50) by laser diffraction using a Mastersizer™ 3000 laser diffraction particle size analyzer manufactured by Malvern Instruments. The total concentration of the four different sizes of thermally conductive filler particles is generally 90% by weight or more, 92% by weight or more, 94% by weight or more, 95% by weight or more, or even 96% by weight or more based on the weight of the composition, and at the same time, 98% by weight or less, 97% by weight or less, 96% by weight or less, or even 95% by weight or less. Generally, the total volume percent (vol%) of the thermal filler is 80 vol% or more, 81 vol% or more, 82 vol% or more, 83 vol% or more, or even 84 vol% or more, based on the volume of the composition, and at the same time, is generally 90 vol% or less, or even 85 vol% or less.
[0026] (i) Large-sized particles. The large-sized thermally conductive filler particles are one type of particles selected from the group selected from aluminum oxide (Al2O3) particles and aluminum nitride (AlN) particles, or a combination of both types of particles. Examples of suitable large-sized filler particles include spherical Al2O3 particles and crushed AlN particles. The "spherical" particles are produced by flame spraying or spraying as taught in JP201202090A. The large-sized thermally conductive filler particles have an average particle size of 70 micrometers or more, 80 micrometers or more, 90 micrometers or more, 100 micrometers or more, 110 micrometers or more, or even 120 micrometers or more, and at the same time 150 micrometers or less, 140 micrometers or less, 130 micrometers or less, 120 micrometers or less, 110 micrometers or less, 100 micrometers or less, 90 micrometers or less, or even 80 micrometers or less. The concentration of the large-sized thermally conductive filler particles in the composition is desirably 25% by weight or more, 30% by weight or more, 32% by weight or more, 34% by weight or more, or even 35% by weight or more, based on the weight of the composition, and at the same time, generally 40% by weight or less, 38% by weight or less, 36% by weight or less, or even 35% by weight or less. Examples of suitable large-sized thermally conductive filler particles include any one or any combination of two or more selected from the group consisting of spherical Al2O3 having an average particle size of 70 to 129 micrometers and crushed AlN particles having an average particle size of 70 micrometers.
[0027] (ii) Medium-sized particles. The medium-sized thermally conductive filler particles are one type of particles selected from the group selected from aluminum oxide (Al2O3) particles and aluminum nitride (AlN) particles, or a combination of both types of particles. Examples of suitable medium-sized thermally conductive filler particles include rounded and spherical Al2O3 particles and spherical AlN particles. Preferably, the medium-sized thermally conductive filler particles are rounded or spherical Al2O3. The "rounded" particles are prepared by mechanically grinding the crushed filler to remove corners, as taught in U.S. Pat. No. 7,789,330. The medium-sized thermally conductive filler particles have an average particle size of 30 micrometers or more, or even 35 micrometers or more, and at the same time 45 micrometers or less, 40 micrometers or less, or even 35 micrometers or less. The concentration of the medium-sized thermally conductive filler particles in the composition is desirably 15% or more, 18% or more, 19% or more, 20% or more, 22% or more, 24% or more, 26% or more, or even 28% or more by weight based on the weight of the composition, and at the same time 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, or even 20% or less by weight. Examples of suitable medium-sized thermally conductive filler particles include any one or any combination of two or more selected from rounded Al2O3 particles having an average particle size of 20 to 35 micrometers, spherical Al2O3 particles having an average particle size of 10 to 45 micrometers, and spherical AlN particles having an average particle size of 30 micrometers.
[0028] (iii) Small-sized particles. The small-sized thermally conductive filler particles are Al2O3 particles, preferably spherical Al2O3 particles. The small-sized thermally conductive filler particles have an average particle size of 1 micrometer or more, 2 micrometers or more, 3 micrometers or more, or even 4 micrometers or more, and at the same time 5 micrometers or less, 4 micrometers or less, or even 3 micrometers or less. The concentration of the small-sized thermally conductive filler particles in the composition is desirably 25 wt% or more, 26 wt% or more, 27 wt% or more, 28 wt% or more, or even 29 wt% or more based on the weight of the composition, and at the same time, generally 32 wt% or less, 31 wt% or less, or even 30 wt% or less. An example of a suitable small-sized thermally conductive filler is spherical Al2O3 with an average particle size of 2 micrometers.
[0029] (iv) Micro-sized particles. The micro-sized thermally conductive filler particles are thermally conductive particles, preferably selected from one or a combination of Al2O3 and zinc oxide (ZnO). Particularly preferably, the micro-sized thermally conductive filler particles are spherical Al2O3 particles and crushed ZnO particles. The micro-sized thermally conductive filler particles have an average particle size of 0.1 micrometers or more, 0.11 micrometers or more, 0.12 micrometers or more, 0.14 micrometers or more, 0.15 micrometers or more, 0.20 micrometers or more, 0.30 micrometers or more, or even 0.40 micrometers or more, and at the same time, 0.50 micrometers or less. The concentration of the fine-sized thermally conductive filler particles in the composition is desirably 10% by weight or more, 11% by weight or more, 12% by weight or more, 13% by weight or more, 14% by weight or more, and at the same time, generally 15% by weight or less, 14% by weight or less, 13% by weight or less, 12% by weight or less, or even 11% by weight or less, based on the weight of the composition. Examples of suitable fine-sized thermally conductive filler particles include crushed ZnO particles having an average particle size of 0.12 micrometers and spherical Al2O3 particles having an average particle size of 0.5 micrometers.
[0030] Surprisingly, the composition of the present invention does not require MgO particles to achieve both a thermal conductivity of 7.5 W / m*K or more, even 8.0 W / m*K or more, and even 9.0 W / m*K or more, and a flow rate of more than 50 g / min in an extrusion rate test. In fact, the composition of the present invention may not include MgO particles having an average particle size of 129 micrometers or more, or even 70 micrometers or more. The composition of the present invention may in fact not include MgO particles at all.
[0031] The composition may optionally contain a catalyst for promoting the reaction (e.g., curing) between polyorganosiloxane molecules. Catalysts include those that promote hydrosilylation reactions and / or those that promote moisture curing reactions. Examples of hydrosilylation catalysts include platinum-based catalysts such as Speier's catalyst (H2PtCl6), Karstedt's catalyst (organoplatinum compounds derived from divinyl-containing disiloxanes), and platinum-based catalysts of 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complexes encapsulated with phenyl resins, as well as rhodium-based Wilkinson's catalyst (tris(triphenylphosphine)rhodium(I)chloride). Moisture curing catalysts include any one or combination of two or more organometallic catalysts selected from the group consisting of titanium compounds, tin compounds, and zirconium compounds. Examples of suitable titanium compounds include tetraisopropyl orthotitanate, tetrabutoxy orthotitanate, di(isopropoxy)bis(ethylacetoacetate)titanium, di(isopropoxy)bis(methylacetoacetate)titanium, and di(isopropoxy)bis(acetylacetonate)titanium. Examples of suitable tin compounds include dibutyltin dilaurate and dibutyltin dioctoate. Examples of suitable zirconium compounds include tetra(isopropoxy)zirconium, tetra(n-butoxy)zirconium, tetra(t-butoxy)zirconium, di(isopropoxy)bis(ethylacetoacetate)zirconium, di(isopropoxy)bis(methylacetoacetate)zirconium, and di(isopropoxy)bis(acetylacetonate)zirconium. When present, typical catalyst concentrations are 0.001% or more, and may be 0.01% or more, 0.10% or more, 0.15% or more by weight based on the weight of the composition, while generally being 0.50% or less, 0.40% or less, 0.30% or less, 0.20% or less by weight.
[0032] The composition may optionally contain an inhibitor. Inhibitors include cure inhibitors known in the art for different cure mechanisms. One example of an inhibitor is methyl(tris(1,1-dimethyl-2-propynyloxy))silane. When present, inhibitors are generally present at a concentration of 0.0001% by weight or more, or 0.001% by weight or more based on the weight of the composition, while generally present at a concentration of 5% by weight or less, or even 1% by weight or less, or even 0.5% by weight or less.
[0033] The compositions of the present invention may (or may not) include any one or any combination of two or more of the additional components selected from the group consisting of antioxidant stabilizers, pigments, viscosity modifiers, fumed silica, and spacer additives. Spacers are non-thermally conductive fillers and have an average particle size in the range of 50 to 250 micrometers. Examples of spacers include glass and polymer beads. Antioxidants, with or without stabilizers, when present, are generally included at a concentration of 0.001 to 1 weight percent of the composition weight. Antioxidants may be present alone or in combination with stabilizers. Antioxidants include phenolic antioxidants and stabilizers include organophosphorus derivatives. Pigments include carbon black and other additives that impart color to the composition. One particularly desirable pigment is copper phthalocyanine because of its ability to impart a blue color and to function as a free radical scavenger. When present, pigments tend to be present at a concentration of 0.0001 to 1 weight percent based on the composition weight.
[0034] The compositions of the present invention are desirably one-part curable compositions, in which the polyorganosiloxane component comprises a combination of a vinyl-capped polydiorganosiloxane and a silylhydride-functional polyorganosiloxane, and an encapsulated platinum catalyst.
[0035] The compositions of the present invention are useful as thermally conductive materials that can be inserted along a thermal path between two objects, and embodiments of the present invention include articles that feature such an arrangement of the compositions of the present invention. For example, the compositions of the present invention can be inserted between a heat-generating object and a heat sink to facilitate the transfer of heat from the heat-generating object to the heat sink. For example, the compositions of the present invention can be inserted between a heat source component (such as a central processing unit (CPU), a graphics processing unit (GPU), or a memory chip) and a heat dissipation component (such as a heat sink, a cooling tube, a cooling plate, etc.) to dissipate heat in electronic devices such as data center servers, communication base stations, smartphones, optical communication modules, and solid state disks. EXAMPLES
[0036] Table 1 discloses the ingredients used in the following samples. Samples 1 to 6 are examples.
[0037] Prepare samples according to the formula listed in Table 2. Combine ingredients (a), (b), and (e) in the cup of a Speed Mixer. Then add ingredient (c) from minimum to maximum and mix for 20 seconds at 1000 RPM, then mix for 20 seconds at 1500 RPM. Add ingredient (d) and mix further. Allow samples to sit at 23 degrees Celsius (°C) for 12 hours before testing. Test each sample by determining its Extrusion Rate (ER) in an Extrusion Rate Test and Thermal Conductivity (TC) in a Thermal Conductivity Test.
[0038] Extrusion Rate Test. Extrusion Rate (ER) is determined using a Nordson EFD dispensing device. The sample material is loaded into a 30 cubic centimeter syringe with a 2.54 millimeter orifice (Nordson EFD Syringe) and 0.62 megapascals of pressure is applied to the syringe to dispense the sample through the orifice. The weight of the sample in grams (g) extruded after 1 minute (min) corresponds to the ER (g / min).
[0039] Thermal conductivity testing. Two hardened blocks of the sample material are prepared for each sample by forming two blocks with dimensions of 29 millimeters (mm) wide by 29 mm long and 8 mm thick, and heating at 120 °C for 60 minutes to harden the blocks of sample material. Thermal conductivity (TC) is measured using the hot disk method using a Hotdisk transient technology sensor C5501 from Hot Disk AB, Gothenburg, Sweden. A heating time of 3-5 seconds and a power of 350-500 milliwatts are used. TC is measured by placing a planar sensor between the two hardened blocks. A fine-tuned analysis is used with temperature drift compensation and time correction selected between 50-150 data points.
[0040] The sample formulations and the ER and TC results for those samples are shown in Table 2. The value for each component is the weight percent of that component in the formulation.
[0041] Samples 1 to 7 show that when containing a combination of four thermally conductive fillers over the range claimed in the present invention, the composition can achieve an ER value of greater than 50 g / min and also achieve a TC of greater than 7.5 W / m*K.
[0042] Samples 8 and 9 show that when the medium sized thermally conductive filler has an average particle size less than 30 micrometers, the TC drops below 7.5 W / m*K, and when the particle size is reduced to 10 micrometers, the ER also drops significantly below 50 g / min.
[0043] Samples 10 and 11 show that when the medium size filler is not present and the amount of large size filler is increased to 50% or more by weight of the composition, the viscosity of the composition becomes too high. Sample 10 is a paste and cannot be extruded. Sample 11 can be extruded but has a low ER value. [Table 1] [Table 2]
Claims
1. 1. A flowable silicone composition comprising: a. a polyorganosiloxane component comprising one or a combination of two or more polyorganosiloxanes; b. a filler treating agent comprising an alkyltrialkoxysilane and a trialkoxysiloxy-terminated diorganopolysiloxane; c. 90 to 98 weight percent of a thermally conductive filler combination, i. 25 to 40 weight percent of thermally conductive filler particles having an average particle size of 70 to 150 micrometers and selected from one or a combination of aluminum oxide and aluminum nitride particles; ii. 15 to 30 weight percent of thermally conductive filler particles having an average particle size in the range of 30 to 45 micrometers and selected from one or a combination of aluminum oxide and aluminum nitride particles; iii. 25 to 32 weight percent aluminum oxide particles having an average particle size in the range of 1 to 5 micrometers; and iv. 10 to 15 weight percent of thermally conductive filler particles having an average particle size in the range of 0.1 to 0.5 micrometers and being one or more selected from the group consisting of aluminum oxide particles and zinc oxide particles; The composition, wherein the weight percentages are based on the weight of the composition.
2. 10. The composition of claim 1, wherein the polyorganosiloxane component comprises a combination of a vinyl-capped polydiorganosiloxane and a silylhydride-functional polyorganosiloxane.
3. 3. The composition of claim 1, wherein the alkyltrialkoxysilane is an alkyltrimethoxysilane.
4. The composition of any one of claims 1 to 3, wherein the alkyl of the alkyltrialkoxysilane is an alkyl or substituted alkyl containing 6 to 18 carbons.
5. The composition of any one of claims 1 to 4, wherein the trialkoxysiloxy-terminated diorganopolysiloxane is a trimethoxysiloxy-terminated dimethylpolysiloxane.
6. The trialkoxysiloxy-terminated diorganopolysiloxane has the following formula: R 3 SiO-(R 2 SiO) d -[(CH 2 ) e ((CH 3 ) 2 SiO) f ] g -(CH 2 ) e -Si(OR”) 3 having 6. The composition of any one of claims 1 to 5, wherein R is independently, in each occurrence, selected from hydrocarbyl groups having 1 to 12 carbons; R″ is a hydrocarbyl having 1 to 10 carbon atoms; subscript “d” has a value in the range of 10 to 150; subscript “e” independently, in each occurrence, has a value of 0; subscript “f” has a value of 0 to 6, and subscript “g” has a value of 0 to 6.
7. The composition of any one of claims 1 to 6, wherein the composition does not contain magnesium oxide particles having an average particle size greater than 70 micrometers.
8. 2. The composition of claim 1, wherein the composition is a one-part curable composition and the polyorganosiloxane component comprises a combination of a vinyl-capped polydiorganosiloxane and a silylhydride-functional polyorganosiloxane, and an encapsulated platinum catalyst.
9. An article of manufacture comprising the composition of any one of claims 1 to 8 interposed along a thermal path between two objects.
Citation Information
Patent Citations
Thermally conductive silicone composition and cured product of the same
JP2017210518A
Thermally conductive silicone composition and cured product of the same, and electronic device and method for manufacturing the same
JP2018076423A
Thermally conductive composition
WO2016190188A1
Thermally conductive resin composition, heat dissipation sheet, heat dissipation member and method for producing same
WO2018131486A1
Multicomponent-curable thermally-conductive silicone gel composition, thermally-conductive member and heat dissipation structure
WO2019021826A1